The Influence of Work Environment, Work Discipline and Motivation on Employee Performance at PT Tiki Jalur Nugraha Ekakurir (JNE) Amplas Trade Center Medan - Yovie Ernanda; Jusrin Efrata; Yossy Pratiwi; Trisafira Harahap; Hayanti Harefa (Enrichment : Journal of Management, 2022)
PT Tiki Jalur Nugraha Ekakurir (JNE) Amplas Trade Center Medan is one of the shipping companies in Indonesia. One of the most important factors in the development of PT Tiki Jalur Nugraha Ekakurir (JNE) Amplas Trade Center Medan is human resources. Based on employee performance data in 2019-2020, it shows a decrease in employee performance in the "According to Standard" category with a total of 46 employees and an increase in the number of employees "Not Meeting Standard" with a total of 3 employees. This can be caused by several factors, namely the state of the work environment, the relationship between employees, the level of employee discipline, and the motivation or encouragement of each employee. Based on these problems, it is necessary to research the above factors. In the results of the study, it was concluded that partially and simultaneously the work environment, work discipline, and motivation had a positive and significant effect on the performance of employees of PT Tiki Jalur Nugraha Ekakurir (JNE) Amplas Trade Center Medan.